Audit Tools and Linked Archive System (ATLAS) in the Process of Preparing Audit Working Papers: Approach with the End User Computing Satisfaction (EUCS) Model" - Ni Luh Manik Darmayani (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to investigate the factors that influence user satisfaction with the ATLAS application for preparing Audit Working Papers, utilizing the Computing End User Satisfaction (EUCS) model. It adopts a quantitative approach with a sample of 83 auditors from KAPs in East Java Province who use the ATLAS application, selected through convenience sampling. Data analysis was performed using Partial Least Squares with SmartPLS 2.0. The findings suggest that content, accuracy, format, and timeliness positively affect user satisfaction with the ATLAS application for preparing Audit Working Papers. However, ease of use does not significantly impact auditor satisfaction as an application user.